Peran Karang Taruna dalam Pembinaan Generasi Muda menurut Peraturan Menteri Sosial Nomor 23 Tahun 2013 ( Studi Kasus Karang Taruna Galow Tunas Bangsa Desa Lowayu Kecamtan Dukun Kabupaten Gresik Tahun 2022) - Maslakhul Falaq; Moh. Sa’diyin (JOSH: Journal of Sharia, 2023)
Karang Taruna is a community organization that accommodates young people and women to participate in building villages, in any case, Karang Taruna itself is only filled by youths who have empathy for village progress. According to the Regulation of the Minister of Social Affairs No. 23 of 201, This study aims to answer, describe, and analyze the formulation of the problem, namely How is the youth organization Galow Tunas Bangsa, Lowayu Village, Dukun District, Gresik Regency in fostering the younger generation and what are the obstacles that affect the process of fostering the younger generation.The research method used in this study is a qualitative research method with a descriptive approach where the researcher goes directly to the field where the object of research and research instruments are used to collect data is by conducting an observation, interview and documentation. The results of this study concluded: First, the activities of the Youth Organization of Lowayu Village that have been and are still running are (a) Religious Activities, (b) Sports and Arts Activities, (c) Youth Empowerment Activities. The two obstacles faced by the Youth Organization of Lowayu Village in fostering the younger generation in Lowayu Village are the lack of youth awareness and the difficulty of dividing time between daily activities and activities and work programs carried out by the Youth Organization of Lowayu Village and the difficulty of finding cadres/ administrators who can be active in Karang Taruna activities so that activities are hampered and less than optimal.